Interaction of turbulent structures with ethanol sprays in mixture formation processes in a constant-flow chamber. - Berti, Rafael da Cruz Ribeiro (2018)
The study in formation and evolution of sprays is essential for developing more detailed physical models and new injection strategies for direct injection internal combustion engines. In the present work, the sprays from a multi-hole injector are evaluated in an effort to characterize the effects of the spray development in a constant surrounding air flow. These interactions are studied in terms of the air turbulence characteristics, the inlet air mass flow and the fuel injection pressure. Ethanol sprays are injected in a constant-flow chamber. The apparatus purpose is to isolate the experiment from the fluid flow properties intrinsic to engine operations, such as instabilities and moving walls. The factors that affects the air-spray interactions were assessed with the air velocity fields in the presence of the ethanol spray. The two-phase particle image velocimetry technique was enhanced to allow measuring in the required experimental conditions. In all conditions, the interaction is based in a pressure gradient formed between the inner and outer regions of the spray. The results indicates a different mechanism when compared to quiescent conditions. The recirculation vortex at the spray border is present only in the initial injection stages. However, the end of injection transient, an instability initiated with the injector needle closing, is still present for these conditions. The interaction mechanism accelerates the velocity distributions towards the spray main boundary. The experiments indicate that the increase of the air mass flow modifies the air penetration velocity but without altering the interaction mechanism characteristics. Higher injection pressures suggests a lower degree of air interaction at the initial instants of the spray development. Turbulent intensity distributions are calculated for the air flow during the injection event. The distributions indicate that the sprays attenuate the turbulent intensity in all conditions, consistent with the observations of the velocity fields. To assess the effects of air turbulence, sets of interchangeable perforated plates are used to limit the integral scales of turbulence. The spectrogram analyses indicate turbulence is reduced not only in the integral scales, but also in all the measured frequency scales. The inlet turbulence integral scales of the air flow have little influence in the spray development. In the turbulence field, the power levels at the end of injection were similar regardless of the inlet turbulence integral scales.